Innovation and Adoption of Electronic Business Technologies - Kai Sülzle (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2006)
This paper presents a duopoly model of e-business technology adoption. A leader and a follower benefit from a new e-business technology with uncertain quality depending on its innovation and adoption cost and both firms adoption timing. When innovation and adoption require large set-up costs, the leader favors quick adoption by the follower. The follower prefers either late or no adoption. This is due to a delayed first-mover benefit which stems from an innovators capability to impose a new technology standard. It is shown that inter-firm adoption subsidies are a viable tool to quicken adoption.
Keywords: L10; O31; 330; Electronic business; adoption; innovation; network effects